Characteristics of upper extremity's muscle strength in Turkish national wheelchair basketball players team - Akinoglu, B.; Kocahan, T. (Journal of Exercise Rehabilitation, 2017)
The objective of this study was to reveal characteristics of muscle strength of upper extremities of wheelchair (WC) basketball players and to ensure more-specific training program preparation. Isokinetic muscle strength of 12 WC basketball players were assessed by ISOMED 2000 device. The assessment protocol was evaluated at 60°/sec velocity with 5 times repeated force and at 240°/sec with 15 times repeated force. This protocol was carried out individually for shoulder flexion-extension and wrist flexion-extension movements at the right and left extremities. The flexion/extension ratio was determined to be outside of the ratios accepted as normal for primarily shoulder joint and for wrist joint. The extension movement was stronger than flexion movement in the shoulders at both velocities and the flexion movement was stronger than ex-tension movement in the wrist. The repeat times where the peak torque occurred were 2-3 repeats at 60°/sec velocity during flexion and extension movements for the wrist and shoulders, and the peak torque occurred at an average of 5-6 repeats in the shoulders at 240°/sec velocity and it occurred at 3-4 repeats in the wrist. The angles where the peak torque of the shoulder flexion and extension occurred varied between 80°-115° at both velocities, and it varied between 5°-30° angles for the wrist. As this study revealed, determination of muscle strength characteristics of WC athletes and especially using objective isokinetic devices will guide the planning of the appropriate training and exercise programs and preventing sports injuries in long term.